2019
DOI: 10.31234/osf.io/9w6jp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decision making in slow and rapid reaching: Sacrificing success to minimize effort

Abstract: Current studies on visuomotor decision making come to inconsistent conclusions regarding the optimality with which these decisions are made. When executing rapid reaching movements under uncertainty, humans seem to automatically select optimal movement paths that take into account the position of all potential targets (spatial averaging). In contrast, humans rarely employ optimal strategies when making decisions on whether to pursue two action goals simultaneously or prioritise one goal over another. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
4
3
0
Order By: Relevance
“…In the current study, the execution of the detection aspect of the task responded to the motivation manipulation and showed clear improvements, but the decision about where to look in preparation for the task was unchanged. A similar dissociation is reported in [30], where participants performed rapid reaches towards pairs of lights, one of which was only revealed to be the target after the movement had begun. In these experiments, participants were able to weigh up possible movement plans and select those which minimised mechanical effort.…”
Section: Discussionsupporting
confidence: 81%
“…In the current study, the execution of the detection aspect of the task responded to the motivation manipulation and showed clear improvements, but the decision about where to look in preparation for the task was unchanged. A similar dissociation is reported in [30], where participants performed rapid reaches towards pairs of lights, one of which was only revealed to be the target after the movement had begun. In these experiments, participants were able to weigh up possible movement plans and select those which minimised mechanical effort.…”
Section: Discussionsupporting
confidence: 81%
“…3A). This resulted in more initial and final decision errors during interception, supporting recent evidence that decision-making is impaired when the movement required is more demanding to perform (Hesse et al, 2020;Reynaud et al, 2020). The dorsal and ventral streams are driven predominantly by magnocellular and parvocellular inputs, respectively, and axons of parvocellular cells have slower conduction velocity than magnocellular cells (Maunsell et al, 1999).…”
Section: Visuomotor Decision Errors Suggest Impaired Ventral-dorsal Stream Processing In Older Adultssupporting
confidence: 76%
“…In order to transfer user preferences from one assembly task to another, we want to model the preferences based on features that are task-agnostic. Previous studies [14], [16], [17] have shown that users prefer to minimize movements during task execution. We expect the same for users in an assembly task, i.e., users would prefer to minimize movements required to perform the assembly.…”
Section: B Factors Affecting Human Preferences In Physical Tasksmentioning
confidence: 99%
“…Inspired from prior work in economy of human movement [14], [16], [17], we presume that users would try to minimize their movement throughout the task. Because the set of actions is fixed in our assembly tasks, users can minimize their movement when they switch from one action to the next.…”
Section: B Modeling User Preferences Over Abstract Featuresmentioning
confidence: 99%
See 1 more Smart Citation